2015
DOI: 10.1186/s12888-015-0548-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective cohort study of the relationship between neuro-cognition, social cognition and violence in forensic patients with schizophrenia and schizoaffective disorder

Abstract: BackgroundThere is a broad literature suggesting that cognitive difficulties are associated with violence across a variety of groups. Although neurocognitive and social cognitive deficits are core features of schizophrenia, evidence of a relationship between cognitive impairments and violence within this patient population has been mixed.MethodsWe prospectively examined whether neurocognition and social cognition predicted inpatient violence amongst patients with schizophrenia and schizoaffective disorder (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 90 publications
1
71
3
Order By: Relevance
“…Similarly, the prevalence of individuals who had an episode of inpatient violence was alarmingly high at 42.2%. Assessed violence proneness was just slightly higher than that seen within previous literature [21,62], however, direct comparison of assessed violence proneness using the HCR-20 is difficult due to cross-culture and service variabilities. Nonetheless, these results highlight the startling prevalence of harm to self and others documented within the present sample.…”
Section: Prevalence Of Self-harm and Violencecontrasting
confidence: 59%
See 1 more Smart Citation
“…Similarly, the prevalence of individuals who had an episode of inpatient violence was alarmingly high at 42.2%. Assessed violence proneness was just slightly higher than that seen within previous literature [21,62], however, direct comparison of assessed violence proneness using the HCR-20 is difficult due to cross-culture and service variabilities. Nonetheless, these results highlight the startling prevalence of harm to self and others documented within the present sample.…”
Section: Prevalence Of Self-harm and Violencecontrasting
confidence: 59%
“…Schizophrenia is commonly the most prevalent diagnosis in forensic psychiatry inpatients and, while a majority of those diagnosed are not violent, a diagnosis of schizophrenia is now recognised as conferring an increased risk for violence and aggression in comparison to the general population [18][19]. This increased risk has been attributed to symptomology, comorbidities, cognitive abilities and neurobiology [18][19][20][21], highlighting the wide array of underpinning mechanisms. A diagnosis of schizophrenia is also associated with significantly increased risk of self-harm in both men and women, with comorbid substance abuse significantly increasing this risk [22][23].…”
Section: Risk Factors For Violence and Self-harmmentioning
confidence: 99%
“…Contrary to our hypothesis, vSZ patients outperformed controls on executive tasks in a manner that has been found in the past (Lapierre et al, 1995;Rasmussen et al, 1995).…”
Section: Prediction Of Aggression During 1 Year Follow-upcontrasting
confidence: 55%
“…Current psychopathology, social reasoning and functioning have also been reported to be linked to violence (Serper et al, 2008;O'Reilly et al, 2015), though a recent meta-analysis found that only global cognitive impairment and lack of insight predicted violence in schizophrenia (Reinharth et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence supports an association between violence and delusions and hallucinations (Coid et al, 2013;Keers et al, 2014;Ullrich et al, 2014) but the form and content of the associated moral reasoning has not been investigated. Understanding whether impaired neurocognitive ability and moral cognition in schizophrenia are associated with serious violence could have implications for risk assessment and treatment (O'Reilly et al, 2015).…”
Section: Dear Editormentioning
confidence: 99%